Memanfaatkan Ekosistem Kewirausahaan Sebagai Sistem Sumber Daya Manusia: Studi Kasus pada Perusahaan Startup di Indonesia - Anisah Anisah; Eka Wahyu Hidayat; Ferdian Arie Bowo (Syntax Idea)
This research aims to analyze how startup companies in Indonesia can leverage the entrepreneurship ecosystem as a human resource system. The entrepreneurship ecosystem is a network consisting of startup companies, universities, government, investors, and various other stakeholders that contribute to the creation and facilitation of startup company growth. By focusing on human resource development through the entrepreneurship ecosystem, this research will identify important factors influencing the relationship between startup companies and the ecosystem.